Complete heart block after balloon dilatation for congenital pulmonary stenosis. Issue 3 (March 1988) - Lo, R N; Lau, K C; Leung, M P
Abstract : Permanent complete heart block developed in a five year old child during balloon dilatation for pulmonary valve stenosis. Damage to the atrioventricular node by pressure from the inflated balloon may have caused the conduction defect.